2016
DOI: 10.7759/cureus.945
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening for High-Risk Patients of Different Ages and Risk - Which Modality Is Most Effective?

Abstract: While the guidelines for breast cancer screening in average-risk women are well established, screening in high-risk women is not as clear. For women with BRCA1 or BRCA2 mutations, current guidelines recommend screening by clinical breast examination and mammography starting at age 30. For certain high-risk women, additional screening with magnetic resonance imaging (MRI) is encouraged. This review focuses on differentiating imaging modalities used for screening women at high-risk for breast cancer over the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…Although breast MRI has been shown to be effective, it is important to emphasize that breast MRI is not meant to replace mammography [18]. Moreover, the combined use of both modalities has proven to be the most cost-effective choice in some populations [19]. For these reasons, multiple modality assessments should be considered for any woman with or without Motiva Implants® and Q Inside™ Safety Technology.…”
Section: Discussionmentioning
confidence: 99%
“…Although breast MRI has been shown to be effective, it is important to emphasize that breast MRI is not meant to replace mammography [18]. Moreover, the combined use of both modalities has proven to be the most cost-effective choice in some populations [19]. For these reasons, multiple modality assessments should be considered for any woman with or without Motiva Implants® and Q Inside™ Safety Technology.…”
Section: Discussionmentioning
confidence: 99%
“…Women with a history of chest wall radiation (i.e., mantle radiation for treatment of Hodgkin's lymphoma) at age 30 or younger have an annual mammography and breast screening MRI starting 5 to 10 years after radiation given, but starting no earlier than age 25 and no later than age 40. For women with BRCA1 or BRCA2 genes mutations, current guidelines recommend annual screening by clinical breast examination and mammography starting at age 30 [44]. However, these approaches may vary from country to country.…”
Section: Breast Cancer Screening By Mammography: An Evolutionmentioning
confidence: 99%
“…Therefore, magnetic resonance imaging can be used along with mammography in these women to increase sensitivity of the screening program. Regarding the high-risk individuals with BRCA1 or BRCA2 mutations, current guidelines suggest to begin annual MRI imaging at age 25 and to add mammography at age 30 [44]. Recent meta-analysis of Phi et al [62] showed that additional screening sensitivity from mammography above that from MRI is limited in BRCA1 mutation carriers.…”
Section: High-risk Womenmentioning
confidence: 99%
“…This is exemplified in breast, lung, and colorectal cancer screening programs [39][40][41]. In addition, the use of MRI as a supplemental imaging modality for women at high risk of breast cancer has been found to be very effective in detection even though latest studies suggests its uptake is not as high as expected [42,43]. Screening, as it is today (eg, breast and AAA screening) is based, at least partly, on the thinking that it is more cost-effective to pick up and treat diseases sooner than later in the targeted population.…”
Section: Medical Imagingmentioning
confidence: 99%